Association between sleep quality and mental health among IIUM medical students during COVID-19 - Ahmad Ashhar, Muhammad Ikmal Arif; Razman, Amalia Izzati; Anuar, Muhammad Ashraf Fithri; Abdullah, Muhammad Haikal; Ahmad Haridan, Ahmad Zhareff Emir; Nor Azlan, Nur Khairunnisa; Mohamad, Mohammad Muaz; Shahrir, Shahida Athirah; Mohd Nizam, Najiha Syahida; Johari, Muhammad Luqman ‘Afif; Zulkifli, Ahmad Najmi Abid; Zamani, Muhammad Razin; et al. (2021)
Medical students usually sacrifice their sleep to adjust to their workloads. It is worth noting the importance of a good night's sleep to ensure the body and mind's optimum performance. However, depriving oneself of much-needed sleep in exchange for productivity has been shown to have deleterious consequences on the students' physical health and their state of mind. The objective of this study was to investigate the association between sleep quality and mental health among International Islamic University Malaysia (IIUM) medical students in the COVID-19 era. A cross-sectional study was conducted from July 2021 until August 2021 in IIUM and all year 1 and year 2 medical students were invited to participate. A total of 158 students responded, consisting of 77 first-year and 81 second-year medical students. The survey was distributed to assess the sleep quality using Pittsburgh Sleep Quality Index (PSQI), the mental health status was measured using WHO-Five Well Being Index (WHO-5) for the depression level and the General Anxiety Disorder-7 (GAD-7) for the anxiety level. The association between sleep quality and mental health was tested using Pearson's chi-square test and Fisher's Exact test. The findings showed a significant association between sleep quality and the mental health of medical students. A higher proportion of participants (86.4%) with depressive symptoms had poor sleep quality. Similarly, 81.8% of participants with anxiety symptoms had poor sleep quality. There was significant association between sleep quality and depression and/or anxiety (p<0.001). This study has shown a significant association between sleep quality and mental health status among IIUM medical students. It is highly recommended that the university provide interventions including advertising good sleep hygiene and coping mechanisms to support students' mental health in this COVID-19 era.